Cultivating Interest in Reading and Writing Through Short Stories in Elementary School Students in Temiyang Village, Kroya District, Indramayu Regency - Nurmaelinda (El-Ma'wa: Journal of Arabic, Translation and Linguistic, 2025)
This article is a report on Community Service (PkM) activities aimed at addressing the low interest in reading and writing among elementary school students in Temiyang Village, Kroya District, Indramayu Regency. This low interest in reading is influenced by students' boredom with conventional learning methods and lack of parental attention. The solution implemented is a creative and fun learning program using Story Books (Short Stories) and digital presentation applications (PowerPoint). This program was implemented on July 15, 2024, at the Group 7 Post in Temiyang Village, involving students in grades 1 to 6 of SD Negeri 2 Temiyang. The methods used were lectures, discussions, and practice, and were evaluated using pretests and posttests. The results of data analysis using the N-Gain Test showed a significant increase in understanding and interest. The average N-Gain score was 0.82 (81.74%) which was categorized as "Effective" for improving students' understanding in reading learning. This increase was also supported by an average posttest score of 93.00. The conclusion of this activity is that the use of storybooks as teaching materials has proven effective in fostering students' interest in reading and writing, despite challenges such as the persistence of students who are not yet fluent readers.